STUDYING THE CONDITION OF HAIR FALLS IN PATIENTS WITH HAIR THINKING AND IDENTIFYING MICROMARKERS OF DIFFERENT TYPES OF ALOPICES - Narzikulov R.M.; Saloxitdinov (PEDAGOGS, 2024)
Abstract: The task set before us for writing this article was to study the condition of hair follicles in patients with hair thinning and to identify micromarkers of various types of alopecia. To achieve our goals and objectives, we analyzed 2110 patients under our supervision for 7 years - 714 men and 1396 women, aged from 21 to 53 years. Of which, androgenetic alopecia accounted for 1169 people - 55.4%, diffuse alopecia - 798 people (37.8%), focal alopecia - 144 people (6.8%). The duration of hair loss ranged from 1 month (mainly in patients with alopecia areata) to 3 years. As a result, we came to the conclusion that miniaturization and deformation of the anagen bulb, an increased number of hairs in the telogen stage, as well as a decrease in the diameter of the bulb relative to the hair shaft are not only the most common , but also universal microscopic signs for all types of hair loss. Aplasia of the bulb, as an extreme degree of dystrophy, and trichomalacia occurred mainly with alopecia areata in a progressive stage. Normal anagen, as a microscopic sign of hair health, was observed in our patients with alopecia, as one would expect, extremely rarely.